Psychosocial risks prevention – Perspectives from Portuguese SMEs - Ramos, S.; Costa, P.; Silva, S.A.; Passos, A. M.; Tavares, S. M. (12th EAOHP Conference (“Occupational health psychology in times of change: society and the workplace”)., 2016)
Introduction: This paper presents the Portuguese results from the first phase of the PPPSER project, which has a qualitative nature. Micro, small and medium enterprises (SMEs) represent 99.9% of the Portuguese business setting. According to national sources, there are 1,167,811 SMEs in Portugal, with a combined turnover of 220 billion euros. Therefore, the main goal of this phase was to gather data from relevant SMEs stakeholders about what they perceived as psychosocial risks, their main causes and consequences, the general level of awareness about the issue, the main obstacles to prevention and intervention and specific actions developed considering those risks. Methodology: After developing the interview protocol and defining common guidelines for all countries, the Portuguese team conducted 12 semi structures individual interviews and 3 focus group. Data was analyzed through content analysis Results: Although almost interviewees recognized the relevance of this topic for individuals, companies and society, the assessment, management and prevention of psychosocial risks is still unusual, particularly in SMEs. Participants also stressed the importance of disseminating concrete examples of good practices. Discussion: While health and safety is already an integral part of the management philosophy in most SME’s, the introduction of preventive actions beyond legal requirements still need improvement. The project revealed a low level of awareness about psychosocial risks, the 132 almost inexistence of risk assessment practices and a lack of resources for investing in its prevention. To facilitate the change in the prevention practices it is critical to develop resources that organizations could easily use at a low cost .